The pertussis hypothesis: Bordetella pertussis colonization in the etiology of asthma and diseases of allergic sensitization. (November 2018) - Rubin, Keith; Glazer, Steven
Abstract: Decades of peer reviewed evidence demonstrate that: 1) Bordetella pertussis and pertussis toxin are potent adjuvants, inducing asthma and allergic sensitization in animal models of human disease, 2) Bordetella pertussis often colonizes the human nasopharynx, and is well documented in highly pertussis-vaccinated populations and 3) in children, a history of whooping cough increases the risk of asthma and allergic sensitization disease. We build on these observations with six case studies and offer a pertussis-based explanation for the rapid rise in allergic disease in former East Germany following the fall of the Berlin Wall; the current asthma, peanut allergy, and anaphylaxis epidemics in the United States; the correlation between the risk of asthma and gross national income per capita by country; the lower risk of asthma and allergy in children raised on farms; and the reduced risk of atopy with increased family size and later sibling birth order. To organize the evidence for the pertussis hypothesis, we apply the Bradford Hill criteria to the association between Bordetella pertussis and asthma and allergic sensitization disease. We propose that, contrary to conventional wisdom that nasopharyngeal Bordetella pertussis colonizing infections are harmless, subclinical Bordetella pertussis colonization is an important cause of asthma and diseases of allergic sensitization.